Pengaruh Audit Internal dalam Menciptakan Good Corporate Governance - Rina Deviani; Anastasia Puspitasari; Fadia Affadar; Vani Basaria; Rahmat Agus Santoso (CV. Ulil Albab Corp, 2024)
This research aims to find out and review previous research on the relationship between a good internal audit function to realize Good Corporate Governance in preventing, detecting and reducing fraud. This research uses qualitative methods with a literature study approach to strengthen arguments with information collected in books and articles published in national journals. This research found that based on mapping previous research findings, many have proven that having a good internal audit function within the company has an impact on the implementation of Good Corporate Governance and has an important role in governance by helping monitor risks and detect areas that increase management risk